Proses Penerbitan Dokumen Statement Of Fact (SOF) Mv. Skatzoura Oleh Pt. Lampung Shipping Agency Bandar Lampung - Dedy Sahala Tua Aruan; Suratni Ginting; Lilis Lilis; Fadiyah Hani Sabila (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
This research aims to find out the process of publishing an MV statement of fact (SOF) document. Skatzoura by PT. Lampung Shipping Agency Bandar Lampung. The method used in collecting and writing this paper uses the field research method in library research to find out the flow of the process of issuing a Statement of Fact (SOF) at PT. Lampung Shipping Agency includes several stages, including collecting initial data from shipping activities, coordinating with related parties such as ship captains, shipping agents and port authorities, as well as preparing documents in accordance with applicable standards. The research results show that the effectiveness of the Statement of Fact (SOF) issuance process is greatly influenced by good communication between all parties, as well as a deep understanding of shipping procedures and applicable regulations. In addition, this paper also identifies challenges faced in the process, such as delays in data collection and lack of coordination between parties. The conclusion of this study recommends the need to improve information systems and training for human resources at PT. Lampung Shipping Agency to expedite the process of issuing Statement Of Fact (SOF) documents in the future.